2018
DOI: 10.1017/aap.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization as Mediation

Abstract: In this essay, we examine the potentials and challenges of mobile computing for a core activity of archaeological laboratory research—the typological analysis of ceramics. We discuss the collaborative development, implementation, and evaluation of the PAZC Ceramics module in the FAIMS Mobile platform. Our deployment of the module yielded significant improvements in the efficiency of data collection, as well as reduced numbers of missing fields and higher user satisfaction scores. However, it did not improve da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…The advantages and disadvantages of a paperless workflow using tablet computers has been well documented in the literature (Austin 2014;Caraher 2016;Ellis 2016;Fee et al 2013;Gordon et al 2016;Lindsay and Kong 2020;Motz 2016;VanValkenburgh et al 2018;Wallrodt 2016;Wallrodt et al 2015). Many have found that recording archaeological data using paperless methods has saved time and resources, improved data quality and integrity, and enabled rapid data availability and access.…”
Section: Developing Digital Formsmentioning
confidence: 97%
See 1 more Smart Citation
“…The advantages and disadvantages of a paperless workflow using tablet computers has been well documented in the literature (Austin 2014;Caraher 2016;Ellis 2016;Fee et al 2013;Gordon et al 2016;Lindsay and Kong 2020;Motz 2016;VanValkenburgh et al 2018;Wallrodt 2016;Wallrodt et al 2015). Many have found that recording archaeological data using paperless methods has saved time and resources, improved data quality and integrity, and enabled rapid data availability and access.…”
Section: Developing Digital Formsmentioning
confidence: 97%
“…Instead of researchers spending weeks or months inputting field observations into a database, the data arrive in ready-to-analyze condition through the careful use of smart forms that standardize data capture, which not only eliminates data inconsistencies and typos but also helps in avoiding issues of illegible handwriting, limited space for recording comments, or running out of copies of forms in the field (Austin 2014:14). Scholars who have compared paperless methods to traditional data collection methods in lab settings have found that digital forms improve efficiency and data quality (Austin 2014;VanValkenburgh et al 2018).…”
Section: Developing Digital Formsmentioning
confidence: 99%
“…Many archaeological works dealt with the research of archaeological finds of pottery, for example, Dewar and Marsh [7], Harush et al [8], Van Valkenburgh et al [9], Pecci et al [10] and others, but their findings were based only on archaeological methods. In terms of spatial analysis, archaeological sites are described, for example, in the work of Papworth et al [11], who dealt with spatial statistics and modeling of archaeological finds using laser scanning methods.…”
Section: Introductionmentioning
confidence: 99%